Interaction of Global-Scale Atmospheric Vortices: Modeling Based on Hamiltonian Dynamic System of Antipodal Point Vortices on Rotating Sphere - Mokhov, Igor I.; Chefranov, Sergey G.; Chefranov, Alexander G. (Elsevier Science Bv, 2013)
It is shown for the first time that only an antipodal vortex pair (APV) is the elementary singular vortex object on the rotating sphere compatible with the hydrodynamic equations. The exact weak solution of the absolute vorticity equation on the rotating sphere is obtained in the form of Hamiltonian dynamic system for N interacting APVs. This is the first model describing interaction of Barrett vortices corresponding to atmospheric centers of action (ACA). In particular, new steady-state conditions for N = 2 are obtained. These analytical conditions are used for the analysis of coupled cyclone-anticyclone ACAs over oceans in the Northern Hemisphere. (C) 2013 The Authors. Published by Elsevier B.V.
IUTAM Symposium on Waves in Fluids - Effects of Nonlinearity, Rotation, Stratification and Dissipation -- JUN 18-22, 2012 -- Moscow, RUSSIA
Keywords: point vortices pairs; rotating sphere; atmospheric centers of action; blockings